YogaKids. 2 [videorecording (DVD)] : ABC's for ages 3-6 - Landon, Ted; Wenig, Marsha (Gaiam, 2003)
From alligator to zebra, Yoga ABC's guides a child through 26 playful kid-style poses, movements, and games inspired by animals, flowers, and other familiar icons kids love. Includes abc play that teaches kids about nature and more, kid-friendly ways to build physical fitness and self confidence, and activities to build coordination.